Injury prevalence and associated factors among Japanese lacrosse collegiate athletes - Kimura, Takeshi; Mącznik, Aleksandra Katarzyna; Kinoda, Akira; Yamada, Yuichi; Muramoto, Yuki; Katsumata, Yoshinori; Sato, Kazuki (Frontiers in Sports and Active Living, 2024)
Sports injuries have a substantial impact on athletes' performance and health. To reduce the risk of an injury occurring, the prevalence, localization, and severity need to be established.To examine the prevalence of sports injuries in collegiate lacrosse athletes.Descriptive Epidemiology Study using online survey design.Japanese universities associated with UNIVAS.A total of 1,689 Japanese collegiate lacrosse athletes, 978 females and 701 males.Athletes were surveyed on the injuries within the previous year, their severity, localization, and onset characteristics. The support of an athletic trainer and its association with the odds of sustaining an injury was assessed. Factors related to injuries were explored.Male sex, higher year at the university, and support from an athletic trainer were identified as factors related to higher odds of sustaining an injury and practicing at least 5 days per week was associated with lower odds of sustaining an injury.Male sex athletes, and athletes at the higher year at university are especially at risk of sustaining a lacrosse injury. The aspects of training (e.g., frequency, volume) should be investigated across the athlete development process to address these findings. Further investigation is needed to determine the extent to which the support of athletic trainers affects both the frequency and severity of injuries in lacrosse athletes.